KRITIK SASTRA DI PRANCIS - Muhammad Al-Fayyadl (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The emergence of literary criticism, as sort of “literary institution” in a modern sense, is relatively a new phenomenon in France as it happened in 19th century and would be more institutionalized in 20th century. It due to the progressive distinction between the author criticism and the critic cricitism as well as to the decline of poetic representation, which has been built on hierarchy of genres and critic’s superiority over authors in 17th century. This article traces the institutionalization of literary criticism and the duality of its practices through the lens of Roland Barthes’ “two criticism”, applied to read the practices of literary criticism in France from 16th century onwards. Keywords: literary criticism, “two criticism”, crisis.